IMPLIKASI PELAKSANAAN SURAT EDARAN MAHKAMAH AGUNG (SEMA) NOMOR 3 TAHUN 2014 TERHADAP EKSISTENSI UNDANG – UNDANG NOMOR 1 TAHUN 1974 - Adi Syahputra Sirait (IAIN Padangsidimpuan, 2018)
Supreme Court Circular (SEMA) number 3 in 2014 concerns about inspection of case voluntary of marriage confirmation, it’s a solution for the problems that occur in all districts /cities in Indonesia related to Population Administration which is a mandate of Law Number 23 of 2006 and Presidential Regulation Number 25 of 2008, the circular letter is still a reference for Religious Courts in Indonesia to determine marriages that are not registered by the Office of Religious Affairs. In substantially, SEMA can reveal the problems that’s the individual rights of the Indonesian people about attendance, protection and recognition of the determination of the legal status of a person, but on the other hand SEMA has implications for the existence of Law Number 1 of 1974 which still has a rule and reference in implementation of marriage in Indonesia. The Circular Letter of Supreme Court (SEMA) is basically a technical guideline or implementation manual that must be submit to the principles of Lex Specialis Derogat Legi Generalis. So that it cannot be contradicted with the Law, moreover it can weaken the implementation of the law.